A dominantly inherited malformation syndrome with short stature, upper limb anomaly, minor craniofacial anomalies, and absence of TBX5 mutations: Report of a Thai family - Kantaputra P.N. (2014)
We report on a Thai family with dominantly inherited malformation syndrome with upper limb anomalies, short stature, quadricuspid aortic valve, and minor craniofacial anomalies. The affected individuals comprised a mildly affected mother, a moderately affected daughter, and a most severely affected son. The daughter and son had short stature. The craniofacial abnormalities comprised frontal bossing, hypoplastic nasal bones, depressed nasal bridge, and broad nasal alae. The upper limb defects varies among the patients, ranging from radial ray defects in the mother through radial and ulnar ray defects with unilateral humeral hypoplasia in the daughter to radial ray defects with severe oligodactyly and bilateral humeral hypoplasia in the son. All patients in this family had hypoplasia of the shoulder girdle and resembled what is observed in many families with Holt-Oram syndrome. Moreover, the son showed quadricuspid aortic valve with mild aortic regurgitation. However, the present family did not show any mutation of the TBX5 gene, a diseasecausing gene of Holt-Oram syndrome. The present family deserves further investigation on other genes that play a role in the development of the upper limbs, particularly of radial rays. © 2002 Wiley-Liss, Inc.